2019
DOI: 10.31603/pharmacy.v5i1.2625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Education Home Pharmacy Care on Hypertension Patients ‘Living Quality in Puskesmas

Abstract: Hypertension is one of ten degenerative diseases that decline the patient’s quality of life. Controlling hypertension through the role of pharmacists as a care giver in home pharmacy care activities can reduce the morbidity of the disease. The purpose of this study was to examine the effect of home pharmacy care education on the quality of life of hypertensive patients hospitalized at the Gamping II Public Health Center. This research design was quasi-experimental with a pre post control group. Respondents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…The results of the study on the effect of home pharmacy care education on blood pressure control and knowledge level of hypertensive patients at Kendalsari Public Health Center Malang are presented in Table I Previous studies have shown that increased renin release, which can lead to increased blood pressure, occurs when the estrogen-to-androgen ratio decreases in older women (Utami et al, 2019). This is also supported by other studies that state that High-Density Lipoprotein (HDL) levels in the blood protect against cardiovascular disease in women because of estrogen, but estrogen levels decrease during menopause, making women more susceptible to cardiovascular disease (Pramestutie & Silviana, 2016).…”
Section: Results and Discussion Description Of Respondent's Character...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study on the effect of home pharmacy care education on blood pressure control and knowledge level of hypertensive patients at Kendalsari Public Health Center Malang are presented in Table I Previous studies have shown that increased renin release, which can lead to increased blood pressure, occurs when the estrogen-to-androgen ratio decreases in older women (Utami et al, 2019). This is also supported by other studies that state that High-Density Lipoprotein (HDL) levels in the blood protect against cardiovascular disease in women because of estrogen, but estrogen levels decrease during menopause, making women more susceptible to cardiovascular disease (Pramestutie & Silviana, 2016).…”
Section: Results and Discussion Description Of Respondent's Character...mentioning
confidence: 99%
“…[299][300][301][302][303][304][305][306][307][308] Previous research has shown that home pharmacy care affects patient compliance when taking medication, and can also control patient blood pressure (Gibran et al, 2021). Likewise, research conducted at Gamping Health Centre II shows that individuals with hypertension in community health centers can benefit from home pharmacy care explanations and can significantly reduce high systolic and diastolic values (Utami et al, 2019). However, in practice, Indonesians apply less home pharmacy care because there are still obstacles, one of which is the lack of information on how to implement it.…”
Section: Introductionmentioning
confidence: 99%
“…Fokus Home Pharmacy Care pada penyakit tidak menular berdasarkan data bahwa penyakit ini memerlukan pengobatan jangka panjang dan beresiko pada kepatuhan pasien dalam meminum obat (Silalahi, 2019;Permatasari et al, 2019;Utami et al, 2019). Resiko yang lain adalah kesalahan penggunaan obat akibat polifarmasi.…”
Section: Hasil Dan Pembahasanunclassified
“…pengobatannya yang bersifat seumur hidup dan memerlukan manejemen harian dalam jangka waktu yang lama (Utami et al, 2019).…”
unclassified